FAKTOR KEUANGAN DAN NON KEUANGAN YANG MEMPENGARUHI UNDERPRICING PADA PERUSAHAAN YANG MELAKUKAN PENAWARAN UMUM PERDANA DI BURSA EFEK INDONESIA, BURSA MALAYSIA, DAN BURSA SINGAPURA - Jenny Vivianti (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to test and to analyze the association of return on assets, debt to equity ratio, firm size, proceeds, firm age, inflation rate, and interest rate either partially or simultaneously, to initial return of firm that doing initial public offering at Indonesian Stock Exchange, Malaysian Exchange, and Singapore Exchange in the period of 2009-2012. The method used is multiple regression analysis using SPSS 20. The result show that only proceeds influence with underpricing at Indonesian Stock Exchange and only firm age influence with underpricing at Malaysian Exchange. Meanwhile, return on assets, debt to equity ratio, firm size, proceeds, firm age, inflation rate, and interest rate influence simultaneously at Indonesian Stock Exchange and Singapore Exchange. Thus, investor may consider proceeds in making decisions that related to their investment in indonesian.